ISOLATION OF CHITOSAN SNAIL SHELL (Achatina fulica F) ON CHEMICAL CHARACTERISTICS AND BACTERIA OF Staphylococcus aureus KIRBY BAUER IN VITRO METHOD - Umar Umar; Surahmaida Surahmaida; Rio Alta; Rizka Surya Ningrum (Universitas Islam Negeri Mataram, 2019)
The shell of snail contains chitin that can be transformed into chitosan through four stages, which are deproteination, demineralization, depigmentation, and deacetylation. Chitosan can be utilized as an antibacterial agent because it has amine groups. In this research, chitosan that prepared from the snail shell will be analyzed using FT-IR spectroscopy to determine the deacetylation degree (DD). The antibacterial activity test result of Staphylococcus aureus will be carried out on chitosan with various concentrations using in-vitro Kirby Bauer method and will be analyzed using One Way ANOVA with confidence level at 95%. The variations concentration of chitosan used is 300, 400, 500, 600, and 700 ppm. The result shows that the deacetylation degree of chitosan is 63.09% and the optimum concentration of chitosan that can inhibit the Staphylococcus aureus bacteria is 500 ppm with diameter inhibition is 34.33 mm.